Structural reinforcement in townhouses by covering masonry with welded mesh and mortar (Gaceta Técnica, 2022)
In the research presented here, the structural behavior of two semi-detached houses built informally was evaluated, which showed various structural problems such as knocking, short columns and column discontinuity. The mechanical properties of the materials and soil were determined by means of in situ and laboratory tests. Subsequently, the analysis was carried out using mathematical models, which were calibrated with periods taken from environmental vibrations. At this stage, it was found that the structures did not exhibit adequate behavior to resist gravitational and seismic forces, so the reinforcement of both structures by means of masonry veneer was proposed; in addition, it was proposed to join both houses at the slab level with metal plates. To eliminate the knocking problem. Finally, the proposed reinforcement was evaluated and it was shown that the veneer stiffened the structures allowing them to meet the requirements established by current regulations at low cost
Keywords: masonry veneer; semi-detached houses; coated masonry; welded mesh